The “Ivy-Sign” in Moyamoya Disease—From MRI Pattern to Diagnosis - Gburek-Augustat, Janina; Sorge, Ina; Merkenschlager, Andreas (Neuropediatrics, 2020)
Moyamoya disease (MMD) is characterized by bilateral, chronic progressive stenosis at the terminal portions of the internal carotid arteries and their proximal branches. The “smoke-like” appearance of the arterial collaterals in angiography gives the disease its name. The “ivy-sign” is the less-known magnetic resonance imaging (MRI) pattern of this disease. The leptomeningeal collaterals present as diffuse signal enhancement at the brain surface in contrast-enhanced T1-weighted image and fluid-attenuated inversion recovery sequences “as if overgrown with ivy.”We report on three patients with MMD in whom the “ivy-sign” was already present but misinterpreted in the initial MRI of the brain. The correct diagnosis was made only after repeated MRI.Using three case studies, we describe the difficulties in the interpretation of the “ivy-sign” as an MRI pattern. Knowledge of the “ivy-sign” can be helpful, especially in diseases predisposing to MMD. If this MRI pattern is present, MMD should be considered and MR angiography should be added.
Keywords: ivy-sign; leptomeningeal collaterals; moyamoya; vasculopathy; MRI; MR angiography; childhood stroke